A qualitative analysis evaluating how medical students perceive COVID-19 pandemic and its impact on their lives: Life in the Pandemic - AYVAZ, İLKNUR; GİRGİN, ŞEVKET; LÜLECİ, NİMET EMEL; HIDIROĞLU, SEYHAN; TOPUZOĞLU, AHMET; SAVE, DİLŞAD; KARAVUŞ, MELDA (My University, 2023)
One of the groups experiencing the pandemic’s effects were students. This study was aimed to evaluate the effects of the COVID-19 pandemic on the lives of medical students and also to see their perspectives about the pandemic. This study is designed as a qualitative study. In-depth interviews were conducted with 30 medical students on an online platform in February 2022, at the end of the third peak period. A semi-structured question guide used as a data collection tool. First, questions about individual characteristics then open-ended questions about their COVID-19 pandemic perception and its impact on their lives were asked. The thematic analysis method was used and \"Life in the pandemic\" were grouped into two main themes: 1.Perception of the Pandemic and Consequent Impact on Life and 2. Pandemic Period and Its Impact on Life. The median age was 22. Half of the participants have been diagnosed with COVID-19. All of the participants were vaccinated. In this study it has been observed that the majority of the medical students have perceived the COVID-19 pandemic as a difficult period and also as a new, uncertain and adverse situation. Another adverse effect perceived by the majority was restriction of social life. Fear and anxiety were most commonly used to express their mood during the pandemic. During the pandemic students individual, mental and social lives are highly affected. While negative effects are generally seen during the social isolation process, this situation has eased with the normalisation of the process.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); COVID-19; Medical students; Pandemic; Qualitative study